1999
DOI: 10.1006/iilr.1999.0110
|View full text |Cite
|
Sign up to set email alerts
|

The Information Needs and Seeking Habits of Lawyers in England: A Pilot Study

Abstract: A B ST R AC TThis article investigates the information needs and seeking habits of lawyers in England in the United Kingdom. Speci¢cally, it seeks to ascertain the type of information lawyers require to meet their needs; the reasons prompting them to seek information; to establish from where lawyers obtain information; and to determine the factors that in£uence their information needs and seeking habits. This study was carried out as part of a wider research project for a doctorate programme. Data collection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
3
15
0
Order By: Relevance
“…Devadson and Lingman (1997) also opined that identification of needs and seeking behaviour is necessary for the provision of effective information services. Otike (1999) conducted a study on the information needs and seeking behaviour of lawyers in England with the aim of determining the sources of information they used in meeting their needs, and the factors that influenced their information-seeking behaviour. The findings indicated that the lawyers' information needs were greatly influenced by the kinds of jobs they do.…”
Section: Importance Of Information To Lawyersmentioning
confidence: 99%
“…Devadson and Lingman (1997) also opined that identification of needs and seeking behaviour is necessary for the provision of effective information services. Otike (1999) conducted a study on the information needs and seeking behaviour of lawyers in England with the aim of determining the sources of information they used in meeting their needs, and the factors that influenced their information-seeking behaviour. The findings indicated that the lawyers' information needs were greatly influenced by the kinds of jobs they do.…”
Section: Importance Of Information To Lawyersmentioning
confidence: 99%
“…Adefolaju, (1989) modestly compares the knowledge he had gained as principal for seven years with the grasp of the requirements of the job which he had as a newly appointed principal, and concluded that the difference was too much to be imagined. Otike (1999) investigated the information needs and seeking behavior of engineers he posited that engineers and experienced ones do not require much information for enhancement as the younger and newly qualified ones.…”
Section: Working Experience and Utilisation Of Information Resourcesmentioning
confidence: 99%
“…Within these studies is (Otike, 1999) in which he summarizes the major work done on the information needs of lawyers in England and their information browsing habits. The findings of this research showed that the information needs of lawyers are strongly influenced by the nature of their work, where experience is invaluable and influence in their needs, depending largely from printed sources and electronic resources were less used.…”
Section: Information Behavior In Political Studies Researchersmentioning
confidence: 99%